Pengaruh Pembiayaan, Pengelolaan Keuangan Dan Peran Fasilitator Pendamping Terhadap Pengembangan Usaha Nasabah - Saputri, Anis; Hendri, Nedi; Zanaria, Yulita (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to determine the influence of financing, financial management and the role of facilitators on customer business development (case study on BTPN Syariah MMS Metro Pusat customers). This study uses quantitative research through a descriptive statistical approach. Using primary data through data collection techniques with questionnaires and has a population of 120 respondents from Bank BTPN Syariah MMS Metro Pusat customers. The sample was obtained by choosing the Random Sampling Technique, namely sampling from the population is carried out randomly without considering the strata in the population space, until a sample of 54 respondents was obtained. The results of the study show that Financing has an effect on the development of customer businesses. Financial management has an effect on the development of customer businesses. The role of the facilitator has an effect on the development of customer businesses. Financing, Financial management and the role of the facilitator have an effect on the development of MMS Metro Pusat customer businesses